Cryopreservation Effects on Consensus Criteria of Human Mesenchymal Stem Cells: A Review - Dewi Hambar Sari; Sri Suciati Ningsih (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2021)
Broad range applications of human mesenchymal stem cells (MSCs) neccesitate the best way to preserve MSC. Cryopreservation is the only one applicable methods for MSCs storage, which consists of vitrification and slow freezing cryopreservation. However, there is a lack of standard procedure of cryopreservation. Different freezing steps and cryo-mediums are often used, which may impact on MSCs characteristics. This article aims to evaluate the impact of cryopreservation on consensus criteria of MSCs derived from various tissues, which consists of surface morphology, differentiation capacity, and surface marker expression. Twenty-nine in vitro studies were analyzed, and their results organized according to the cell attributes they asses. This review shows that there are various procedures of slow-freezing cryopreservation. Our findings show that a temperature reduction rate of -1oC / min is the most suitable for MSC cryopreservation, and combination of DMSO and FBS in addition of growth medium is still the most used cryomedium in slow freezing cryopreservation. Whereas, in vitrification, combination of ethylene glycol, Ficoll, and sucrose is used as cryoprotective agents. In conclusion, our results show that although there are variations in slow-freezing cryopreservation, there is no significant effect on MSC either morphology, surface marker expression (positive markers consists of CD105, CD90, CD73; and negative markers consists of CD45, CD34, CD14 or CD11b, CD19, and HLA-DR), or differentiation capability (adipogenic, chondrogenic, and osteogenic). Whereas, vitrification effects could not be clearly defined yet, because of a limited number of studies.Key Words: Cryopreservation, Slow-Freezing, Vitrification, MSC characteristiccs, MSC storage